Examining the Acute Effects of Classroom-Based Physical Activity Breaks on Executive Functioning in 11- to 14-Year-Old Children: Single and Additive Moderation Effects of Physical Fitness - Graham, Jeffrey D.; Bremer, Emily; Fenesi, Barbara; Cairney, John (Frontiers in Pediatrics, 2021)
Objective: Research supports the efficacy of acute, classroom-based, physical activity breaks on executive functioning in children. However, research pertaining to the effect of physical fitness on the acute physical activity – executive functioning relationship remains limited. The primary purpose of this study was to investigate the acute effects of classroom-based, teacher delivered, physical activity breaks on executive functioning in 11 to 14-year-old children. We also investigated the potential moderating role of both aerobic and musculoskeletal fitness on the acute physical activity – executive functioning relationship. Method: Participants (N = 116) completed pre- and post-test assessments of executive function assessments (i.e., inhibition, switching, and updating) separated by a classroom-based physical activity break or sedentary classroom work. We manipulated the dose (i.e., length) and type of physical activity breaks. With regards to dose, participants in the experimental conditions engaged in 5-, 10-, or 20-min of physical activity whereas controls completed sedentary classroom math work at their desk. With regards to type, one experimental condition completed traditional physical activity breaks whereas the other experimental condition completed academic physical activity breaks (i.e., performed mental math and physical activity). Participants’ mood, motivation, and self-efficacy were also assessed following the experimental manipulations. Results: Overall, executive function scores improved across each assessment following the physical activity breaks when compared to sedentary classroom work regardless of dose and type. Participants also reported more positive mood states, higher motivation to complete the executive function tests, and higher self-efficacy to perform the executive functions tests following the physical activity breaks. Single moderation analyses showed that low-moderate levels of aerobic fitness moderated the acute physical activity – executive functioning relationship. Additive moderation analysis showed, collectively, that both aerobic and musculoskeletal fitness moderated the acute physical activity – executive function relationship. Conclusion: Findings from the present study provide evidence for the acute effects of short (i.e., 5-20min) classroom-based physical activity breaks on executive functioning and psychological states in children. Results also suggest levels of both aerobic and musculoskeletal fitness moderate these effects, however future research is needed to further elucidate this complex relationship.